Experential Marketing dan Customer Relationship Management Dalam Mempengaruhi Loyalitas Pengguna Jasa Resort Pada Masa Pandemi - Yani, Ahmad; Munir, Miftahul (Universitas Pendidikan Ganesha, 2021)
This study explains the problematic influence of experiential marketing and customer relationship management on the loyalty of restaurant service users during the COVID-19 pandemic which indicates a decrease in the number of customers. The sample in this study were 89 customers of damarmas resort within 6 months of the study. Using accidental sampling technique. Collecting data using questionnaires through instrument validity and reliability tests, using multiple linear regression analysis techniques and hypothesis testing. The results of the research that have been carried out indicate an indication of the influence between experiential marketing and customer Relationship Management partially positive and significant effect on service user loyalty. Simultaneously experiential marketing and customer Relationship Management have a positive and significant effect on the loyalty of service users at Damarmas Resort Kediri.